Mandatory vaccination of infants in France: Is that the way forward? - Henri Partouche; Serge Gilberg; Vincent Renard; Olivier Saint-Lary (European Journal of General Practice, 2019)
In this opinion paper, the authors argue that the extension of mandatory immunization of infants up to two years of age from three diseases (diphtheria, tetanus, poliomyelitis) to 11 diseases, introduced in France in January 2018, is not a sustainable response to the challenge of controlling vaccine-preventable diseases. In France in 2017, infant immunization coverage (IC) rates were sufficiently high or increasing (hepatitis B), except for measles, mumps and rubella (MMR) and meningococcus C disease. Even if vaccination obligation makes it possible to achieve the MMR IC objectives among infants, communication programmes and supported advice from GPs are essential for the catch-up of susceptible adults to obtain herd immunity. The impact of mandatory immunization on hesitancy remains uncertain, and it contradicts the evolution of the patient’s role in the governance of his own health and the principle of autonomy. Numerous studies have shown that interventions and advice from health professionals improve vaccine acceptance. To correct the poor implementation of some vaccination programmes by health professionals, strong communication and resources from health authorities are needed, rather than a retreat towards obligation. Reducing missed opportunities and increasing access to immunization are essential objectives. Finally, an immunization policy based on primary care and a patient-centred approach to each vaccination are more likely to reduce vaccine hesitancy, sustainably.